Aestheticising the Post-Industrial Debris : Industrial Ruins in Contemporary British Landscape Photography - Karolina Kolenda (Revue LISA)
The article concentrates on contemporary British artistic photography and on how it represented industrial and post-industrial sites in the period of de-industrialisation. It starts with the examination of how British photography perpetuated an idealised image of the rural landscape as a locus of national identity. Industry and industrial architecture were excluded from this vision. By the end of the 20th century, de-industrialisation meant that many former industrial sites were demolished or redeveloped. At the same time, a growing appreciation of industrial heritage translated into an increased interest in post-industrial sites, also on the part of photographers. This paper investigates how contemporary landscape photography has sought to introduce the image of industrial ruins into the realm of collective visual imagination by drawing on aesthetic conventions of the Picturesque and the Pictorial, on the one hand, and on the conventions characteristic for developments in contemporary photography (from documentary aesthetics in the work of John Davies, through the “abject” in the work of Richard Billingham and Tom Hunter, to the post-pastoral landscape photography by John Kippin). Contemporary landscape photography attempts to reinstate the image of Britain’s industrial past into commonly shared imagination, where the conflicted nature of the country’s cultural identity – the clash between the “Northern” and “Southern” metaphors – reveals itself with particular force.